A systematic review of ankle fracture-dislocations: Recent update and future prospects - Cao, Mu-Min; Zhang, Yuan-Wei; Hu, Sheng-Ye; Rui, Yun-Feng (Frontiers in Surgery, 2022)
Background: Ankle fracture-dislocations are one of the most severe types of ankle injuries. Compared to the simple ankle fractures, ankle fracture-dislocations are usually more severely traumatized and can cause worse functional outcomes. The purpose of this study was to review the previous literatures to understand the anatomy, mechanisms, treatment, and functional outcomes associated with ankle fracture-dislocations. Methods: The available literatures from January 1985 to December 2021 in three main medical databases were searched and analyzed. The detailed information was extracted for each article, such as researchers, age, gender, groups, type of study, type of center research, level of evidence, significant findings, study aim, cause of injury, time from injury to surgery, type of fracture, direction of dislocation, follow-up, postoperative complications and functional evaluation scores. Results: A total of 15 studies (1089 patients) met the inclusion criteria. Only one study was a prospective randomized trial. The top-ranked cause of injury was high-energy injury (21.3%). Moreover, the most frequent type of fracture in ankle dislocations was supination-external rotation (SER) ankle fracture (43.8%), while the most common directions of dislocation were lateral (50%) and posterior (38.9%). Conclusions: Collectively, most ankle fracture-dislocations are caused by high-energy injuries and usually have poor functional outcomes. The mechanism of injury can be dissected by the ankle anatomy and Lauge-Hansen’s classification. The treatment of ankle fracture-dislocations still requires more detailed and rational solutions due to the urgency of occurrence, the severity of injury, and the postoperative complications.